PERKEMBANGAN TEORI DAN PENELITIAN AKUNTANSI - Zaki Baridwan (Faculty of Economics and Business, Universitas Gadjah Mada, 2000)
The article discusses development in accounting theory and research. Accounting theory was developed later than the practice of double entry bookkeeping. In the early part of the accounting theory development, accounting experts developed the normative theory. The development of positive accounting theory came later. Improvement of theory was performed through research in accounting. As was in the development of accounting theory, development in the accounting research was also started in very simple, non-formal investigation apprroach. The use of deductive and inductive approach resulted in the development of descriptive/positive accounting theory. Accounting theory and research was developed in many different areas, using different theories and concepts from different disciplines such as economics, finance, psychology, sociology etc. The use of those broad concepts as background improved the speed of accounting theory development in the later years. Now we could see that accounting theory is used to explain and predict different phenomena based on results of accounting research that employs concepts from many different disciplines.